Effect of bactericides and bioagents on bacterial wilt of tomato caused by Ralstonia solanacearum and its yield parameters - Sharma, Divya; Singh, Yogendra (Indian Journal of Plant Protection, 2020)
A study was undertaken to evaluate treatments viz., Pseudomonas fluorescens (5 kg/ha), Bacillus subtilis (5 kg/ha), chitosan (1.5g/100ml), chitosan+copper hydroxide (0.7+1g/100ml), streptomycin (64µg/ml), ampicillin (16µg/ml), copper hydroxide (2g/1000ml), Trichoderma harzianum (5kg/ha), Trichoderma harzianum+Pseudomonas fluorescens (5kg/ha) and bleaching powder (15kg/ha) at recommended dosage against bacterial wilt of tomato under glasshouse as well as field conditions during 2015 and 2016. Under field conditions data revealed that, minimum Percent Disease Index (PDI) and percent disease incidence was recorded in bleaching powder treated plots (35.66%, 60%) followed by T.harzianum+P.fluorescens (40.66%, 70%). Maximum PDI and percent disease incidence was recorded in T.harzianum treated plots (65.00%, 86.66%) whereas it was 80.66 and 93.33 per cent in control at 50 DAS. Under glasshouse conditions, minimum PDI and percent disease incidence was recorded in bleaching powder treated pots (36.66%, 50%) followed by T.harzianum+P.fluorescens (42%, 60%). Maximum PDI and percent disease incidence was recorded in streptomycin (58.33%, 90%) and whereas it was 66.83 and 100 per cent in control at 50 DAS. The present study demonstrates the possible role of bactericides and bioagents in controlling bacterial wilt of tomato.